Effect of chitin, chitosan and NaCMC biopolymers on the consistency limits of organic silt - O'Kelly, Brendan (My University, 2024)
With global concerns on carbon emissions, there is increased need for various eco-friendly alternatives to conventional (cement and lime) additives used in ground improvement applications. This paper investigates the effect of three biopoly- mers—chitin, chitosan, and sodium carboxymethyl cellulose (NaCMC)—on the consistency limits of low plasticity organic silt soil. The theory of soil mechanics suggests that understanding the soil’s plasticity nature is helpful in predicting strength and compressibility characteristics. The variation in the Casagrande liquid limit (LL), plastic limit (PL), plasticity index, and flow index of the soil are presented for 0.5–4% chitin and chitosan dosages, and 0.25–1% NaCMC dosage. For all three biopolymers, the consistency limits (more-so for LL than PL) increased with increasing dosage, with NaCMC addition producing a more dramatic effect compared to chitin and chitosan additions. The biopolymer additives formed ‘bridge’ connections between the soil particles, helping to improve strength properties. This bridging effect explains the significant increases in LL (being essentially a strength-based parameter) for biopolymer addition. A greater LL increase was observed for NaCMC addition since it is a gellable biopolymer with moisture retaining property.
PUBLISHED
Keywords: Organic soil; Liquid limit; Plasticity index; Chitin; Chitosan; Cellulose; Smart & Sustainable Planet; Atterberg limits; Biomolecules, Bioplastics, Biopolymers; Biopolymeric Materials; CELLULOSE; CHITIN; CHITOSAN; Environmental Geotechnics; GEOTECHNICAL ENGINEERING; Geotechnics; Ground improvement; Organic soil; Plastic limit; Soil Mechanics; Soil Mechanics & Foundations; bio-geotechnics; fine grained soil; geotechnical; liquid limit; soil classification; soil improvement; soil plasticity; soil stabilization